The role of concentration polarization in ultrafiltration of ovine cheese whey - Macedo, Antónia (2013)
Ultrafiltration of pretreated whey is assessed in terms of permeation patterns for the membranes M1 (ETNA10PP), M2 (GR61PP) and M3 (GR81PP). Permeation experiments were carried out at different transmembrane pressures and cross-flow velocities, for studying the influence of these operating conditions on permeate fluxes. The modeling of ultrafiltration was performed in terms of permeate fluxes adjusting the resistances-in-series model. The results showed that the M1 allows higher permeate fluxes and displays the conventional pattern of linear variation of permeate fluxes with transmembrane pressure for lower pressures. With membranes M2 there is a linear variation of permeate fluxes with transmembrane pressure in all the pressure range and for the three feed circulation velocities studied. The membrane M3 has the lowest permeate fluxes and shows for the two higher feed circulation velocities (0.94 m/s and 1.23 m/s) a linear variation of permeate fluxes with transmembrane pressure, in all the pressure range studied. The modeling of ultrafiltration allowed to conclude that with the membranes M1, the concentration polarization controls the mass transfer in all the pressure range studied, whereas the resistance due to fouling is the main contributor for lowering the permeate fluxes, with the membranes M2 and M3. Once the membranes M1 allow higher permeate fluxes and better selectivity with a negligible contribution of fouling, in the experimental conditions used, they are more suitable for the ultrafiltration of pretreated ovine cheese whey.